Head circumference, leg length and its association with dementia among older adult population in Singapore. (4th January 2017) - Chang, Sherilyn; Ong, Hui Lin; Abdin, Edimansyah; Vaingankar, Janhavi Ajit; Jeyagurunathan, Anitha; Shafie, Saleha; Mahendran, Rathi; Subramaniam, Mythily; Chong, Siow Ann
Abstract : Background: Head circumference and leg length serve as reliable proxy indicators of early‐life environment. Research studies have shown that these anthropometric measurements are associated with cognitive impairment and dementia among older adults. The aim of the present study was to assess the associations between dementia with head circumference and leg length among the older adult population in Singapore. This study also aimed to examine the sociodemographic correlates of these anthropometric measurements. Methods: Data were collected from 2565 older adults aged 60 years and above, in a population study on the Well‐being of the Singapore Elderly. Head circumference and leg length measurements were obtained, and sociodemographic information was recorded. Dementia diagnosis was made using the 10/66 dementia algorithm. Anthropometric measurements were first stratified into quarters, and then logistic regression analysis was used to examine factors associated with head circumference and leg length, as well as to examine the association between dementia with these measurements. Results: Sociodemographic correlates of head circumference and leg length include age, gender, ethnicity and education level. Smaller head circumference was independently associated with higher odds of 10/66 dementia (OR = 2.173–2.709). When the regression analysis was stratified by gender, the association was found only in the male sample. Leg length was not significantly associated with dementia after controlling for sociodemographic variables. Conclusion: Smaller head circumference is independently associated with dementia among older adults in Singapore. Findings from this study suggest that risk factors for dementia begin their influence in early life. Copyright © 2017 John Wiley & Sons, Ltd.